Language acquisition for deaf children: Reducing the harms of zero tolerance to the use of alternative approaches - Humphries Tom; Kushalnagar Poorna; Mathur Gaurav; Napoli Donna; Padden Carol; Rathmann Christian; Smith Scott R (BMC, 2012)
Abstract Children acquire language without instruction as long as they are regularly and meaningfully engaged with an accessible human language. Today, 80% of children born deaf in the developed world are implanted with cochlear devices that allow some of them access to sound in their early years, which helps them to develop speech. However, because of brain plasticity changes during early childhood, children who have not acquired a first language in the early years might never be completely fluent in any language. If they miss this critical period for exposure to a natural language, their subsequent development of the cognitive activities that rely on a solid first language might be underdeveloped, such as literacy, memory organization, and number manipulation. An alternative to speech-exclusive approaches to language acquisition exists in the use of sign languages such as American Sign Language (ASL), where acquiring a sign language is subject to the same time constraints of spoken language development. Unfortunately, so far, these alternatives are caught up in an "either - or" dilemma, leading to a highly polarized conflict about which system families should choose for their children, with little tolerance for alternatives by either side of the debate and widespread misinformation about the evidence and implications for or against either approach. The success rate with cochlear implants is highly variable. This issue is still debated, and as far as we know, there are no reliable predictors for success with implants. Yet families are often advised not to expose their child to sign language. Here absolute positions based on ideology create pressures for parents that might jeopardize the real developmental needs of deaf children. What we do know is that cochlear implants do not offer accessible language to many deaf children. By the time it is clear that the deaf child is not acquiring spoken language with cochlear devices, it might already be past the critical period, and the child runs the risk of becoming linguistically deprived. Linguistic deprivation constitutes multiple personal harms as well as harms to society (in terms of costs to our medical systems and in loss of potential productive societal participation).